2017
DOI: 10.7554/elife.25543
|View full text |Cite
|
Sign up to set email alerts
|

Pioneer neurog1 expressing cells ingress into the otic epithelium and instruct neuronal specification

Abstract: Neural patterning involves regionalised cell specification. Recent studies indicate that cell dynamics play instrumental roles in neural pattern refinement and progression, but the impact of cell behaviour and morphogenesis on neural specification is not understood. Here we combine 4D analysis of cell behaviours with dynamic quantification of proneural expression to uncover the construction of the zebrafish otic neurogenic domain. We identify pioneer cells expressing neurog1 outside the otic epithelium that mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 89 publications
2
15
0
Order By: Relevance
“…The uncovered sequence of events is reminiscent of the pioneer neuron model first proposed over a century ago and which has been observed in various model systems, including Drosophila ( Sánchez-Soriano and Prokop, 2005 ; Lin et al, 1995 ; Jacobs and Goodman, 1989 ), zebrafish ( Hoijman et al, 2017 ; Wanner and Prince, 2013 ), and mouse ( Morante-Oria et al, 2003 ; Stainier and Gilbert, 1990 ). However, a key difference between what we observed and the classical model is that in the zebrafish pancreas these neurons are not migrating toward the target organ where they provide instructional cues for neuronal specification ( Hoijman et al, 2017 ) or lay down axon tracks for the following neurons ( Wanner and Prince, 2013 ). Instead, we observed the migration of these neurons away from the target organ while maintaining contact via neural extensions, which may subsequently provide tracks for other neurons to migrate along to reach their targets.…”
Section: Discussionmentioning
confidence: 97%
“…The uncovered sequence of events is reminiscent of the pioneer neuron model first proposed over a century ago and which has been observed in various model systems, including Drosophila ( Sánchez-Soriano and Prokop, 2005 ; Lin et al, 1995 ; Jacobs and Goodman, 1989 ), zebrafish ( Hoijman et al, 2017 ; Wanner and Prince, 2013 ), and mouse ( Morante-Oria et al, 2003 ; Stainier and Gilbert, 1990 ). However, a key difference between what we observed and the classical model is that in the zebrafish pancreas these neurons are not migrating toward the target organ where they provide instructional cues for neuronal specification ( Hoijman et al, 2017 ) or lay down axon tracks for the following neurons ( Wanner and Prince, 2013 ). Instead, we observed the migration of these neurons away from the target organ while maintaining contact via neural extensions, which may subsequently provide tracks for other neurons to migrate along to reach their targets.…”
Section: Discussionmentioning
confidence: 97%
“…207 In addition to conventional otic neuroblasts, a recent study in zebrafish identified a precocious group of neurog1-expressing neural precursors, termed "pioneer cells," that originate outside the otic placode in a position just lateral to the anterior hindbrain. 214 Arising around 13 hpf, pioneer cells undergo directed migration toward the otic placode and ingress into the neurogenic domain during a short interval from 15 to 17 hpf. After several hours, pioneer cells egress from the otic epithelium and migrate medially to form the first mature neurons in the otic ganglion.…”
Section: Specification Of Neuroblastsmentioning
confidence: 99%
“…211,213 In zebrafish the earliest otic expression of neurog1 occurs by 15 hpf (12 ss) in the anterior-lateral quadrant of the otic placode. 206,214 The otic domain of neurog1 expands greatly after formation of the otic vesicle, with specification peaking around 24 hpf (30 ss) and then rapidly declining over the next 12 hours. Specification and delamination of otic neurons ceases entirely by 42 hpf.…”
Section: Specification Of Neuroblastsmentioning
confidence: 99%
“…Xu et al (84) provide evidence that sensory hair cells and supporting cells in the organ of Corti as well as glial cells in their associated spiral nerve fibers and ganglion share a common progenitor. However, Hoijman et al (87) identify pioneer cells expressing Neu-rog1 outside the otic epithelium that migrate and ingress into the epithelializing placode to become the first otic neuronal progenitors. The authors emphasize that in the neurogenic domain, Neurog1 induces Neurod1 expression, which among others is required for delamination of neuroblasts from the epithelium.…”
Section: Pericytes and The Origin/regeneration Of The Inner Ear Structuresmentioning
confidence: 99%